Ramadan is not the same as Ramadan fasting - Seiermann, Andrea U.; Gabrysch, Sabine (The journal of nutrition, 2020)
To identify children exposed to Ramadan fasting in utero, Tith et al. use Arabic language. We agree with the authors that effect sizes in their study are biased to the null because not all Arabic-speaking women in Canada are Muslim. Nonfasting pregnant women among Muslim Arabs would further dilute the true effect of Ramadan fasting. Adherence to Ramadan fasting during pregnancy in Canada has not been studied, but adherence rates among Muslims in other Western high-income countries have been reported at ∼50% (3, 5, 6). However, complex lifestyle effects of Ramadan in both fasting and nonfasting Muslims cannot be separated from effects of daytime fasting during Ramadan in studies with unknown fasting adherence at the individual level. The effects found by Tith et al. can therefore be interpreted as effects of Ramadan, but not necessarily as effects of Ramadan fasting.